Psychological Dimension in The Design of Islamic Education Learning Technology Based on Piaget's Theory - Ma'ali, Izzul; Budiharjo, Eka; Abidin, Zaenal (Kirana Publisher (KNPub), 2025)
Islamic education in the digital era faces serious challenges in integrating developmentally appropriate learning technology with the psychological needs of students. This study analyzes the design principles of Islamic educational learning technology through the lens of Piaget's cognitive development theory, especially in the concrete operational (7-11 years) and formal operational (12-15 years) phases. Using the library research method with a systematic literature review approach, this study explored 25 primary sources (Sinta 2-Scopus journal, turats such as Iḥyā' 'Ulūm al-Dīn) and applied thematic analysis to identify design patterns that are in harmony with the concepts of schema, assimilation, and accommodation in Piaget's theory. The findings show that 72% of Islamic learning platforms fail to apply the principles of cognitive load management (Sweller, 1988), while gamification-based and augmented reality (AR)-based content has proven to be effective for the concrete operational stage according to the concept of tadrīj (gradual education) in Islam. This study proposes a Piagetian Islamic EdTech Design framework that integrates digital scaffolding with the values of tarbiyah islamiyah. The implications of the study include practical recommendations for madrasah e-learning developers and criticism of the dominance of behaviorist approaches in contemporary Islamic educational technology